Cymbidium densiflorum (Orchidaceae; Epidendroideae; Cymbidieae): a new orchid species from China based on morphological and molecular evidence - Lan, Siren; Chen, Lijun; Chen, Guizhen; Wu, Xinyi; Rao, Wenhui; Zhang, Peiwen; Liu, Zhongjian (Phytotaxa, 2018)
A new orchid species, Cymbidium densiflorum, from Yunnan, China, is described and illustrated here based on morphological and molecular analyses. A detailed comparison between the newly discovered orchid and other members of Cymbidium was conducted. The new plant belongs to C. section Cymbidium and has a pendent inflorescence, thick-coriaceous flowers with two pollinia and rigid leaves, and it differs greatly from all other known species of this section by being a large plant bearing leaves with an acute, oblique apex and producing a long inflorescence with more than 30 purplish brown large flowers, in which the lateral sepals are oblique and narrowly elliptic with a tooth at the apex and narrowly ovate-elliptic petals. A molecular study based on the nuclear ribosomal ITS and plastid matK, rbcL, trnG, trnL and atpI DNA sequence data indicated that C. densiflorum is sister to C. paucifolium.